Penunjukan Vendor Prioritas Dalam Penyediaan Karton Dangerous Goods Untuk Proses Re-Packing - Adik Moechlis; Lira Agusinta; Nofrisel Nofrisel; Edi Abdurachman; Dian Artanti Arubusman (Institut Transportasi dan Logistik Trisakti, 2023)
The objective of this research is to determine the priority suppliers in the repackaging division. The main problem is that there are no results of the assessment of the existing criteria, namely one criterion with other criteria is considered to be superior in selecting a vendor. This study uses the Analytical Hierarchy Process analysis tool. The results of this assessment are the supplier's performance to the company using the AHP method based on the right criteria, namely, Dynastyindo with very good results and World Expert with quite good results. The Dynastyndo vendor is classified as very good for March 2021, while the World Expert vendor can improve its performance further. The key findings are, the criteria that are considered most important at this time are price and both services. So that these two things can be focused which can then be seen in terms of which sub-criteria or indicators need to be repaired from vendors who have problems.Policy recommendations as a follow-up to research that still has limitations, it is necessary to carry out actual vendor assessments for all vendors that work with PT. DG Pack Wahana Multi Logsitk using actual data from the current month.